De Novo Donor-Specific Human Leukocyte Antigen Antibodies in Nonsensitized Kidney Transplant Recipients After T Cell-Mediated Rejection. Issue 5 (May 2015) - Chemouny, Jonathan-Maurice; Suberbielle, Caroline; Rabant, Marion; Zuber, Julien; Alyanakian, Marie-Alexandra; Lebreton, Xavier; Carmagnat, Maryvonnick; Pinheiro, Nathan; Loupy, Alexandre; Van Huyen, Jean-Paul; Timsit, Marc-Olivier; Charron, Dominique; et al.
Abstract : Background: Local inflammation is a potential cause of humoral alloimmune responses in renal transplantation, and de novo donor-specific anti–human leucocyte antigen antibodies (dnDSAs) have been associated with a history of acute rejection. Methods: We investigated the frequencies and consequences of dnDSAs after a first episode of acute T-cell–mediated rejection (index TCMR) in previously unsensitized kidney transplant recipients. Results: Of the 1, 054 patients who underwent kidney transplantation between September 2004 and December 2010 at our center, we identified 75 unsensitized patients with at least one TCMR. Index TCMRs were diagnosed 4.4 ± 6.8 months after transplantation. The dnDSAs were assessed using the highly sensitive single-antigen human leukocyte antigen bead assay 5.1 ± 3.9 months after the index TCMR and were detected in 16 patients (21%). Patients who developed dnDSAs were more likely to have experienced pre-transplant sensitizing events and were indistinguishable in their clinical, biologic, and histologic variables at the time of index TCMR, although the tubulitis scores tended to be higher ( P = 0.079). These patients experienced a significantly higher incidence of subsequent antibody-mediated rejection episodes ( P < 0.001), but reduced death-censored graft survival was not observed after a median follow-up of 5.5 years post-transplantation. Follow-up biopsies revealed increased antibody-mediated changes with significantly higher glomerulitis scores and numerically higher C4d staining scores. Conclusion: Monitoring anti–human leukocyte antigen antibodies after cellular rejection may be useful, especially among patients with a history of pretransplant exposure to alloantigens, to predict subsequent humoral events and their consequences. Abstract : This single-center study shows that previously nonsensitized recipients experiencing a first T cell-mediated rejection and subsequently developing donor-specific HLA antibodies have long-term adverse consequences of increased antibody-mediated rejection and chronic antibody-mediated changes on biopsy. Supplemental digital content is available in the text.